2021
DOI: 10.19044/esj.2021.v17n40p20
|View full text |Cite
|
Sign up to set email alerts
|

Agromorphological Evaluation of 44 lines of Mung Bean (Vigna radiata (L.) Wilczek) Introduced in Burkina Faso

Abstract: Mung bean (Vigna radiata L. Wilczek) is an important annual legume which is well suited to dry areas, like Burkina Faso where it is still an orphan legume. The present study was conducted to evaluate 44 mung bean genotypes introduced in Burkina Faso and to determine genetic diversity in this collection using both quantitative and qualitative traits. A field experiment was conducted in an augmented bloc design with three blocks and an extraearly maturing cowpea variety as check. Data were recorded on six (06) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…The analysis showed that the number of pods/plant, number of seeds/pod, biological yield and harvest index were all positively correlated with seed yield/plant at both the genotypic and phenotypic levels. These outcomes concur with the conclusions of Zida et al [15], Harsh and Priya [16], Thonta et al [17], Salman et al [18], Thanga et al [19], Kate et al [20], Sandhiya et al [21], Sarfaraz et al [22] and Dhunde et al [23].…”
Section: Resultssupporting
confidence: 89%
“…The analysis showed that the number of pods/plant, number of seeds/pod, biological yield and harvest index were all positively correlated with seed yield/plant at both the genotypic and phenotypic levels. These outcomes concur with the conclusions of Zida et al [15], Harsh and Priya [16], Thonta et al [17], Salman et al [18], Thanga et al [19], Kate et al [20], Sandhiya et al [21], Sarfaraz et al [22] and Dhunde et al [23].…”
Section: Resultssupporting
confidence: 89%
“…These results suggest that selecting traits with higher PCV and GCV for further breeding efforts could be more effective. These findings align with previous research by Nitesh et al (2017) for seed yield per plant, harvest index, and number of pods per plant, Tushar kumar et al (2019) and Mariyammal et al [11] for seed yield per plant, Ramakrishnan et al [12], Zida et al [13], and Sineka et al [14] for number of pods per plant.…”
Section: Phenotypic Coefficient Of Variation (Pcv) Genetic Coefficien...supporting
confidence: 91%
“…Indeed, the number of days to 50% fowering varied between 33.67 and 47.33 days with an average of about 40 days for all accessions. However, the authors in [16] found that the number of days to 50% fowering varied between 29 and 48 days with an average of 34.46 on mungbean accessions evaluated in Burkina Faso. Furthermore, the cycle of the 15 accessions studied varied from 82 to 93 days with an average of 88 days.…”
Section: Discussionmentioning
confidence: 98%